Performance evaluation and trends estimation of production and reproduction traits in Frieswal cattle under field progeny testing - R S BARWAL; OLYMPICA SARMA OLYMPICA SARMA; MUBASHIR ALI RATHER; C B SINGH; D KUMAR; A K GHOSH; B N SHAHI (Indian Journal of Animal Sciences)
The objective of animal breeding is to optimize the genetic gain per unit time and to assess this gain per unit time, it is therefore, necessary to separate the environmental component from overall phenotypic gain. The data spanning over a period of nine years (2013-2021), pertaining to Frieswal cattle maintained at Pantnagar centre of AICRP- FPT was analyzed and the overall means of 806.30±6.93, 1084.17±6.93, 277.87±0.17, 12.89±0.07, 3060.12±15.66, 3.51±0.01, 310.53±0.43, 373.15±0.44, 95.28±0.48, 1.46±0.03 and 62.62±0.15 for age at sexual maturity (ASM), age at first calving (AFC), gestation period (GP), test day peak yield (TDPY), 305-days milk yield (305D-MY),fat percentage (FP), lactation length (LL), calving interval (CI), service period (SP), number of services per conception (NSPC) and dry period (DP), respectively. The corresponding overall breeding values for these traits were observed as 800.61, 1064.51, 277.64, 13.02, 3163.24, 3.474, 310.00, 372.58, 94.42, 1.468 and 62.57, respectively. The product moment correlations and Spearman rank correlations ranged from low to very high. The estimated phenotypic, genetic, and environmental trends were in positive direction for ASM, AFC, TDPY, 305D-MY and DP whereas in negative direction for GP, FP, LL, CI, SP and NSPC. The results revealed that improvement in the herd has been achieved with respect to TDPY and 305D-MY, however, some deterioration in traits viz. ASM, AFC, Fat % and DP.